2006
DOI: 10.1892/0891-6640(2006)20[1080:cteobe]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Evidence of Bulla Effusion in Cats with Sinonasal Disease: 2001–2004

Abstract: Findings of this study suggest that auditory canal dysfunction may play a larger role in feline sinonasal disease than was previously recognized. The implications of these findings for management of cats with chronic inflammatory or neoplastic sinonasal disease require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The association between middle ear disease and nasal disease on CT scans in cats has been documented previously . The prevalence of middle ear disease in cats with nasal disease in this earlier study was 28% (13/46), which is similar to the 23% (27/118) found here.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The association between middle ear disease and nasal disease on CT scans in cats has been documented previously . The prevalence of middle ear disease in cats with nasal disease in this earlier study was 28% (13/46), which is similar to the 23% (27/118) found here.…”
Section: Discussionsupporting
confidence: 89%
“…This model potentially mimics some nasal and upper respiratory diseases in which mucosal inflammation and temporary auditory tube obstruction result in middle ear effusion. Viral upper respiratory tract infections may also predispose to bacterial colonization of the nasopharynx and ascending bacterial middle ear infection via the auditory tube …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar changes were found in Cavalier King Charles spaniels, where a greater thickness of the soft palate and reduced nasopharyngeal aperture were significantly associated with subclinical otitis media . Presence of concurrent middle ear pathology in dogs and cats with soft palate abnormalities and bulla effusion in cats with sinonasal disorders has also been reported . Two recent publications reported the presence of middle ear effusion in dogs with trigeminal nerve dysfunction due to denervation of the tensor veli palatine muscle and secondary persistent Eustachian tube obstruction impairing its normal drainage .…”
Section: Discussionmentioning
confidence: 54%